The Effect of Economic Growth, Wages, and Investment on Unemployment in West Java from 2021-2024 - Dzimmi Aisyah Pangareban; Wafiqotul Afwa; Ilham Maulana Mustofa; Rachma Iftitakhul Janah; Qoni’ Fajrika Arifah; Lucia Rita Indrawati; Muh Syaiful Bakhri (Media Ekonomi, 2026)
West Java recorded the highest unemployment rate nationally at 6.75 percent in 2024, despite being an industrial center. This study aims to analyze the influence of economic growth, investment, and minimum wage on the Open Unemployment Rate (UR) in 27 districts/cities of West Java Province for the 2021-2024 period. The study uses a quantitative approach with a static panel data regression method. The selection of models through the Chow Test and the Hausman Test resulted in the Fixed Effect Model (FEM) as the best model. The data is sourced from the Central Statistics Agency of West Java and the Investment Coordinating Board. The estimated results show that economic growth has a positive and significant effect on UR, Investment has a positive and significant effect on UR. On the other hand, the minimum wage has a negative and significant effect on UR. The value of the Adjested R-squared is 00.879436. This study recommends an inclusive growth policy based on labor-intensive sectors, investment selection oriented to the absorption of local labor, and the determination of a competitive minimum wage based on the need for a decent life.